Characterization, Modeling, and Analysis of Organic Light-Emitting Diodes With Different Structures - Chen,HT; Choy,WCH; Hui,SY (IEEE Transactions on Power Electronics, 2015)
This paper demonstrates that organic light-emitting diodes (OLEDs) of different structures can be characterized and modeled using a combination of the photo-electro-thermal (PET) theory and spectral power distribution modeling. The photometric, electrical, thermal, and chromatic properties of OLED devices are incorporated into a model framework so that the performance of the OLED of different structures can be compared. A concept of luminance uniformity over the OLED surfaces is also introduced for comparing OLED with large surface areas. Experimental results are included to verify the OLED models and compare the characteristics of two different OLED samples. Based on the same PET framework, some differences of OLEDs and inorganic LEDs are addressed and discussed.